Axial compressive performance of CFRP confined rectangular CFST columns using high-strength materials with moderate slenderness. (13th September 2021) - Du, Yansheng; Zhang, Yutong; Chen, Zhihua; Yan, Jia-Bao; Zheng, Zihan
Highlights: Axial compressive performance of CFRP confined rectangular CFST columns. Theoretical studies on the axial compressive performance of CFRP confined CFST columns. The bearing capacity and ductility of the CFST column are improved under the CFRP. The calculation method for bearing capacity of CFRP confined CFST column was proposed. Abstract: The bearing capacity of concrete-filled steel tube (CFST) columns can be significantly increased by using high-strength materials. However, the ductility of high-strength CFST columns is reduced due to the brittleness of high-strength concrete and the buckling of thin-walled high-strength steel tubes, especially for slender columns. By wrapping the carbon fiber reinforced polymer (CFRP) to increase the confinement on the steel tube, the ductility can be improved. This paper presents experimental and theoretical studies on the axial compressive performance of CFRP confined rectangular CFST columns using high-strength steel and concrete with moderate slenderness. The influence of the section aspect ratio, concrete strength, and CFRP confinement on the axial behavior was analyzed. The experimental results indicate that the local buckling of CFRP-confined specimens is delayed compared with the unconfined specimens. The horizontal CFRP confinement increases the yield load by 1.5–25.6%, and the peak load by 2.5–11.2%. The bearing capacity and ductility of specimens are improved under the confinement of CFRP. The calculation method for axial compression bearing capacity considering the stability of moderate slender specimens was proposed. The ratio of the experimental results to the calculated value is between 0.86 and 1.09, which verified the accuracy of the calculation method.